Changing Patterns of H6 Influenza Viruses in Hong Kong Poultry Markets. (19th September 2010) - Ozaki, Hiroichi; Guan, Yi; Peiris, Malik; Webster, Robert; Webby, Richard
Abstract : Until 2001, H6N1 influenza viruses in the Hong Kong bird markets were represented by a single stable A/teal/Hong Kong/W312/97-like lineage. Beginning in 2001, despite a reduction in overall prevalence, an increase was observed in the number of H6 viruses isolated from chickens and other hosts. To assess any changes in H6 viruses, we characterized 18 H6 viruses isolated in the Hong Kong bird markets from 2001 to 2003. Experimental data showed that the 2003 H6 viruses had similar infectivity for chickens as did A/teal/HK/W312/97, and they were unable to transmit. Although all hemagglutinin genes were closely related to A/teal/HK/W312/97, 7 isolates were reassortant viruses containing similar gene segments of co-circulating H9N2 or H5N1 viruses. The receptor specificity was different from that of A/teal/Hong Kong/W312/97. Interestingly, similar observations have been documented in H9N2 viruses in Hong Kong. This evolution strongly suggests that some change in the ecology of influenza in the region selected for these changes. Taken together, these findings suggest that the H6 influenza viruses isolated in the Hong Kong markets are not well adapted to chickens and that the likely continued source of these viruses are other "minor" poultry species in which they are undergoing genetic and biologic evolution.